COVID-19 and off label use of drugs: an ethical viewpoint - Shojaei, Amirahmad (Daru, 2020)
BACKGROUND: The COVID-19 outbreak is rapidly spread over the world and kills infected patients. There is no proven medication for its treatment, so, all of the medications used for treatment are considered to be off-label. Off-label uses are not under regulation in the outbreak because there is no specific regulation for this condition. OBJECTIVES: In this short communication we aim at describing two ways of off-label use as clinical practice or investigational use. Further, we will describe the third way of off-label use, we named it pseudo-research and then we will state the most possible ethical challenges of off-label use for better perceptions and responsibility. RESULTS: The WHO considers off-label uses as country-specific. All international regulatory bodies consider off-label prescription as the physician’s responsibility and legal by necessitating some requirements. There is no international guideline for regulating investigational off-label uses as clinical practice. CONCLUSION: There are different types of approaches, none of them is comprehensive and conclusive. Furthermore, respecting the four ethical principles necessitates codification and strict regulation of off-label uses either as clinical practice or investigational. Besides, compilation of a special guideline based on ethical principles especially non-maleficence and autonomy for investigational off-label uses in disasters is highly recommended.